Benthic stable isotopes, biogenic silica and sediment geochemistry of gravity core LV28-34-2 - Dirk Nürnberg (PANGAEA, 2025)
Bound by the Asian continent to the northwest and north and the Kurile-Kamchatka-Island Arc to the east and southeast, the Sea of Okhotsk is the second largest marginal sea of the Pacific. In view of strengthened efforts of better understanding cool climate dynamics, the Sea of Okhotsk became an increasing focus of interest as it plays a key role for the modern hydrology of the NW Pacific, its high primary productivity, and its pronounced seasonality in sea ice coverage. We here provide proxydata from gravity core LV28-3-2. The ~9.6 m-long core was recovered from the Derugin Basin in the northern Sea of Okhotsk (53°51.971 N 146°47.499 E) from 1431 m water depth during R/V Lavrentiev Cruise LV28 in 1998 (doi:10.3289/GEOMAR_REP_82_1999). The proxyrecords cover the last ~150 kyrs at centennial resolution. Sampling and analytical studies were carried out from 3 cm to ~960 cm core depth at ~1-5 cm spatial resolution. Benthic stable oxygen (δ18O, extperthousand VPDB) and carbon isotope analyses (δ13C; extperthousand VPDB) were performed on the foraminiferal species Uvigerina spp.. The stable isotope analyses were run on a Thermo Scientific MAT 253 mass spectrometer with an automated Kiel IV Carbonate Preparation Device at GEOMAR according to standard procedures (c.f. Nürnberg et al., 2008). Biogenic silica (opal) was determined with an automated extraction methode (Müller and Schneider, 1993). High-resolution AVAATECH XRF-scanner element compositions of bulk sediment are also provided.